Optimization and Performance Enhancement of a Miniaturized Rectangular Patch Antenna with Slotted Ground Plane Using Ant Colony Algorithm - Bahlaouane Ibtissam; Belhabib Abdelfettah; Ibnyaich Saida; Zeroual Abdelouhab (ITM Web of Conferences)
This paper introduces a new approach for miniaturizing a rectangular patch antenna to achieve a resonant frequency of 2.45 GHz using the Ant Colony Optimization (ACO) algorithm. Initially, the antenna is designed using conventional methods and then the ground plane structure is optimized by introducing slots using ACO algorithm. The targeted resonant frequency of 2.45 GHz is achieved through an appropriate fitness function. The ACO algorithm is employed to design the optimal shape of the ground plane, resulting in a 50.9% miniaturization rate. The proposed antenna, with dimension of 37.6×33.04×1.6 mm3, will be useful for wireless applications such as Wi-Fi and Bluetooth.